Molecular Programming of Mesodiencephalic Dopaminergic Neuronal Subsets - Marten P. Smidt (Frontiers Media S.A., 2017)
Dopamine neurons of the substantia nigra compacta (SNc) and ventral tegmental area (VTA) are critical components of the neuronal machinery to control emotion and movement in mammals. The slow and gradual death of these neurons as seen in Parkinson's disease has triggered a large investment in research toward unraveling the molecular determinants that are used to generate these neurons and to get an insight in their apparent selective vulnerability. Here, I set out to summarize the current view on the molecular distinctions that exist within this mesodiencephalic dopamine (mdDA) system and elaborate on the molecular programming that is responsible for creating such diversity.